ATRT-06. Atypical Teratoid Rhabdoid Tumors (ATRT): results from a Single Institution in Brazil - São Paulo University. (3rd June 2022) - Barreto, Juliana Silveira; Gomez, Karen Nirit Melo; Dutra, Alvaro Pimenta; De Azambuja, Alessandra Milani Prandini; Cristofani, Lilian Maria; Sanders, Felipe Hada; Petito, Carlo; Baraldi, Helena Espindola; Weltman, Eduardo; Ferraciolli, Suely Fazio; Frassetto, Fernando Pereira; Lucato, Leandro Tavares; et al.
Abstract: OBJECTIVES: Atypical teratoid/rhabdoid tumor (AT/RT) is a rare, highly malignant tumor of the central nervous system with poor prognosis. Nowadays, multimodal management, including surgery, chemotherapy (CMT), radiation therapy (RT) and Bone Marrow Transplantation (BMT). The aim of this study was to assess the experience and survival in a center of reference of treatment in childhood cancer in Brazil. PATIENTS AND METHODS: Medical records of AT/RT patients who underwent surgery from 2008 to 2020 at a center of childhood cancer treatment (ITACI) in São Paulo University were retrospectively reviewed and statistically analyzed. RESULTS: Eight patients (2 males and 6 females) were presented with AT/RTs. Median age during presentation was 22 months (range, 0 - 6 years). Seven patients (88%) were < 18 months and one patient were >18 months. Tumor location was supratentorial in four patients, infratentorial in 2 patients. Kidney disease as the primary diagnosis in 2 patients (25%). Surgical treatment was performed in 4 patients. Seven children underwent total CMT and 3 children were treated with RT. Only 3 patients underwent Autologous Bone Marrow Transplantation (ABMT). The chemotherapy management protocol of the patients was variable: 2 patients received the EU-RHAB protocol, 2 patients received the HEAD START III protocol, 3 patients received chemotherapy in the ICE regimen (Ifosfamide + Carboplatin + Etoposide) and 1 patient received chemotherapy in the CDDP+CTX+VCR (Cyclophosphamide + Cisplatin + Vincristine) regimen. All patients had episodes of neutropenic fever when they received chemotherapy, requiring hospitalization and use of an antibiotic treatment. Among the 8 patients analyzed, all died. CONCLUSIONS: Despite progress in treatment, AT/RT of the CNS disease or primary kidney disease associated with a lack of standardization in a regimen contributes to the dismal prognosis. There is a high mortality in patients with AT/RT, similar to that found in the literature.